Spreadsheet applications in chemistry using Microsoft Excel - Diamond, Dermot. (John Wiley and Sons, 1997)
Introduction to Excel. Statistical functions and regression analysis. Introduction to Macros and VBA. Case studies in quantum chemistry. Case studies in physical chemistry. Importing and processing instrumental data. Processing experimental data using solver. Case studies involving VBA.